Объяснение:
1.
а) (3y - 2)(3y + 2) = 9y² - 4
б) (3y - 1)² = 9y² - 6y + 1
в) (4a + 3k)(4a - 3k) = 16a² - 9k²
2.
(b-8)² - (64 - 6b) = b² - 16b + 64 - 64 + 6b = b² - 10b = b(b - 10)
3.
a) 25 - y² = (5 - y)(5 + y)
б) a² - 6ab + 9b² = a² - 2×1×3ab + (3b)² = (a - 3b)²
4.
36 - (6 - x)² = x(2,5 - x)
36 - (36 - 12x + x²) = 2,5x - x²
12x + x² = 2,5x - x²
2x² + 9,5x = 0
x(2x + 9,5) = 0
x = 0 или 2x = -9,5
x = 0 или x = -4,75
ответ: 0; -4,75
5.
а) (c² - 3a)(3a - c²) = -(3a - c²)(3a - c²) = -(3a-c²)²
б) (3x + x³)² = 9x² + 6x⁴ + x⁶
в) (3 - k)²(k+3)² = (3 - k)²(3+k)² = [(3-k)(3+k)]² = (9 - k²)²
6.
а) (3x - 2)² - (3x - 4)(4 + 3x) = 0
(3x - 2)² + (4 + 3x)² = 0
9x² - 12x + 4 + 16 + 24x + 9x² = 0
12x + 20 = 0
12x = -20
3x = -5
x = -5/3
б) 25y² - 64 = 0
y² = 64/25
y = ± 8/5
7.
а) 36a⁴ - 25a²b² = a²(36a² - 25b²) = a²(6a - 5b)(6a + 5b)
б) (x - 7)² - 81 = (x - 7 - 9)(x - 7 + 9) = (x - 16)(x + 2)
Объяснение:
1) Решениеy=(4·x-9)^5
((4·x-9)^5)' = 20(4·x-9^)4
Поскольку:
((4·x-9)5)' = 5·(4·x-9)^5-^1((4·x-9))' = 20(4·x-9)^4
(4·x-9)' = 4
20(4·x-9)^4
y=(x2-3x+1)7
2) Решение:((x2-3x+1)7)' = (-7·3x·ln(3)+14·x)(x2-3x+1)6
Поскольку:
((x2-3x+1)7)' = 7·(x2-3x+1)7-1((x2-3x+1))' = (-7·3x·ln(3)+14·x)(x2-3x+1)6
(x2-3x+1)' = (x2)' + (-3x)' + (1)' = 2·x + (-3x·ln(3)) = -3x·ln(3)+2·x
(x2)' = 2·x2-1(x)' = 2·x
(x)' = 1
Здесь:
Решение ищем по формуле:
(af(x))' = af(x)*ln(a)*f(x)'
(-3x)' = -3x·ln(3)(x)' = -3x·ln(3)
(x)' = 1
(-7·3x·ln(3)+14·x)(x2-3x+1)6
3) Решение:y=(sin(x))^3
(sin(x)^3)' = 3·sin(x)^2·cos(x)
Поскольку:
(sin(x)^3)' = 3·(sin(x))^3-1((sin(x)))' = 3·sin(x)^2·cos(x)
(sin(x))' = cos(x)
3·sin(x)2·cos(x)
x = 3
Объяснение:
(2х+3)²-(2х-1)(2х+1)=46
4x² + 12x +9 - 4x² + 1 = 46
12x = 36
x = 3